Increased prevalence of fungemia in Medina, Saudi Arabia - Khateb, Aiah M.; Alofi, Fadwa S.; Almutairi, Abdullah Z. (Frontiers in Epidemiology, 2023)
Background The prevalence of fungal infection is increasing globally due to an increase in the immunocompromised and aging population. We investigated epidemiological changes in fungemia in one of the major centers in Medina over seven years period with 87,447 admissions. Methods Retrospective search of records for causative agents of fungemia in inpatients at King Fahad Hospital (KFH) in 2013–2019. Fungal-positive blood cultures, demographic, and treatment data were extracted. Results A total of 331 fungemia episodes proven by blood culture were identified in 46 patients. The annual prevalence of fungemia increased from 0.072 in 2013 to 1.546 patients per 1,000 in 2019. The mean age of fungemia episodes was 56 years, and 62% of episodes occurred in females. Samples from central blood incubated aerobically yielded the highest fungemia rate, accounting for 55% (n = 182). Among yeast species, Candida parapsilosis was responsible for the highest number of episodes 37% (n = 122), followed by Candida glabrata (32%; n = 107), Candid albicans (29%; n = 94), and Cryptococcus neoformans (1%; n = 4). Among molds, Lichtheimia (Absidia) species was the most common (1%; n = 3). Yeast-like fungi Trichosporion mucoides accounted for (0.003% n = 1). The use of antifungal treatment has increased (96%) over the years (2013–2019). An increase in resistance rate of 2% was found in C. albicans and C. glabrata. The most prevalent comorbidity was renal disease (24.2%). Conclusions C. parapsilosis was the leading cause of fungemia. The association of renal disease with increased candidemia was alarming. This study is a fundamental resource to establish management policies for fungal infection in the region.